Ask Question
2 April, 22:37

Simplify the expression.

(-8i) (2i)

0
Answers (1)
  1. 2 April, 23:33
    0
    Answer: 16

    Step-by-step explanation:

    = (-8i) (2i)

    = (-8*2) (i^2)

    = - 16 * - 1 (NOTE THAT i^2 = - 1)

    = 16
Know the Answer?
Not Sure About the Answer?
Get an answer to your question ✅ “Simplify the expression. (-8i) (2i) ...” in 📙 Mathematics if there is no answer or all answers are wrong, use a search bar and try to find the answer among similar questions.
Search for Other Answers